A New Calibration Technique for Autocollimator by using a Small Angle Generator and Laser Interferometer - Chinchusak, Wanchai; Tipsuwanaporn, Vittaya; Tagheen, Pochaman (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Solitons in a nonlinear dual-core coupler can be in symmetric, antisymmetric, and also asymmetric states. There are two branches of asymmetric states. For one of the branches we apply perturbation theory to give an approximate expression for the soliton states near the ends of the branch, and combine the results to give a Padé approximant for the whole branch. Using a perturbative technique involving the regrouping of algebraically secular terms developed by us previously, we can analyse one end of the other branch. However, the remaining end does not appear to be amenable to this type of analysis. Keywords: - Corresponding author: E-mail: s2061151@kmitl.ac.th , ktvittay@kmitl.ac.th , pochaman@mail.dss.go.th